HUBUNGAN ANTARA RELIGIUSITAS DENGAN SELF CONCEPT PADA IBU BEKERJA YANG MEMILIKI BALITA - rini hartati (Psychopolytan : Jurnal Psikologi, 2018)
This study aims to see the relationship between religiosity and self concept in working mothers who have toddlers. This research can be useful for the development of clinical psychology and Islamic psychology, as well as motivation for working mothers who have toddlers about the importance of increasing religiosity in shaping a mother's self concept. This research uses quantitative methods. The measuring instrument that will be used in this study is using a psychological scale that is related to self concept and religiosity. Self concept is someone's knowledge and ideas about themselves and attitudes towards themselves and their behavior. Calhoun and Acocella (in Desmita, 2010) mention 3 dimensions of self concept, namely knowledge, hope and judgment. From these 3 dimensions can see how the self concept of working mothers who have toddlers. The research data was processed using the product moment Pearson correlation coefficient. The results showed a relationship between religiosity and self concept in working mothers who have toddlers (p = 0.028). Keywords: religiosity, self concept, working mother